PENGARUH MEDIA SOSIAL INSTAGRAM @wisatadakwahokura TERHADAP MINAT BERKUNJUNG FOLLOWERS - Wicaksono, M. Arif; ", Rumyeni (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Social Media Instagram is one of the media that often used in activity in promotion activity through internet in this modern era. Promotional activities is an effort to introduce products to consumers with the aim to achieve the achievement of a positive perspective. The introduction of products through social media instagram is a source of information that can attract interest to consumers. The purpose of this research is to know how much influence of social media instagram Dakwah okura tourism on followers intention to visit with using S-R theory as a grounded theory.This research used methods of quantitative research explanatory approach to the presentation of qualitative analysis. This research was conducted by sending a questionnaire to followers online. Subjects in this research are 92 people who follows social media instagram @wisatadakwahokura and the category is determined based on random sampling. Data collection was obtained through questionnaires and documentation. Data analysis technique in this research is quantitative analysis.The results showed that social media instagram of @wisatadakwahokura impact followers intention to visit. Evidenced by the regression coefficient value of this research is Y = 6.919 + 0.689X. Constant number of 6.919 and the variable coefficient value of social media for 0.689. Meanwhile t 6.919is greater than the t tabel of 1.660, with a significance level of 0.000 is smaller than Î± = 0,05. According to the â€œModel Summaryâ€ table shows that the value of R = 0.757 and coefficient of determination (Rsquare) is equal to 0.573. the figure shows the understanding that the contribution of the effect of variable social media instagram @wisatadakwahokura on followers intention to visit amounted to 57.30%. Social Media Instagram @wisatadakwahokura effects on followers intention to visit, and the influence of the category â€œstrongâ€.Keywords: Influence, Instagram, Intention